2011
DOI: 10.3109/19390211.2011.627783
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review of Cinnamon (Cinnamomumspp.) by the Natural Standard Research Collaboration

Abstract: An evidence-based systematic review of cinnamon (Cinnamomum spp.), including written and statistical analysis of scientific literature, expert opinion, folkloric precedent, history, pharmacology, kinetics/dynamics, interactions, adverse effects, toxicology, and dosing, by the Natural Standard Research Collaboration is discussed in this monograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 449 publications
2
34
0
3
Order By: Relevance
“…Activation of various isoforms lowers levels of plasma triglycerides, elevates levels of HDL-C, and increases insulin sensitivity. 3 Glucose transport by the glucose transporters (GLUT), more specifically GLUT4, is also a primary target of diabetes research. Current research suggests that facilitating translocation through GLUT4 will increase glucose uptake and utilization, benefitting hyperglycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of various isoforms lowers levels of plasma triglycerides, elevates levels of HDL-C, and increases insulin sensitivity. 3 Glucose transport by the glucose transporters (GLUT), more specifically GLUT4, is also a primary target of diabetes research. Current research suggests that facilitating translocation through GLUT4 will increase glucose uptake and utilization, benefitting hyperglycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…2 These possible effects may be a concern for patients with impaired liver function, concurrent anticoagulant or antiplatelet therapy, patients on antilipidemic agents, and those who are known to be hypersensitive to cinnamon or its components. There are reports of nonimmunologic contact urticaria occurring in people coming into contact with cinnamon products 3 ; however, because no human studies have been conducted to test this theory, these concerns remain hypothetical. Although our meta-analysis did not address safety data because the reporting of adverse events and tolerability were not consistent among the RCTs, all the included trials stated that no significant side effects were seen with cinnamon use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinnamon (Cinnamomum cassia) has become a natural product of interest because it has been hypothesized to provide health benefits, for example the ability to reduce blood glucose and levels of serum lipids. It has been suggested that the effect of cinnamon on blood glucose can be attributed to its active component cinnamaldehyde [9]. Cinnamon has been of research interest for patients with diabetes since the 1990s, when peroxisome proliferator-activated receptors (PPARs) were recognized as a possible therapeutic target for diabetes and dyslipidemia [10].…”
Section: T2dmmentioning
confidence: 99%
“…Therefore, it was used to treat dry and itchy throat, productive cough, thirst, aphonia, dysuria, and interference of defecation [33]. The tongue grass moisturized the tissues and was anti-inflammatory, relieving cough and asthma [34]. The maidenhair fern possessed the functions of anti-inflammation and detoxification, relieving cough and eliminating phlegm, mitigating asthma and pain.…”
Section: Discussionmentioning
confidence: 99%